ETHICS OF ENGINEERS: CHALLENGES OF COMPETENCY FORMATION AND ASSESSMENT - Yulia V. Gasheva (Высшее образование в России, 2016)
The paper covers issues of ethical education for engineering students in Russian universities. The topical character of these issues is grounded by the findings of the survey of self-study reports on degree engineering programs, presented within professional accreditationrun by the Association for Engineering Education of Russia in 2003-2013, and reports of the program auditors. The proposed solution involves integration of an ethical aspect into professional disciplines assuming understanding of codes of engineering ethics by students and applying principles of the codes as one of the criteria for assessment of students’ projects. Authors outline the most effective methods of teaching engineering ethics and proposeindicators for relevant competency assessment.